Rates of urinary catheter-associated urinary tract infection in Saudi MOH hospitals: a 2-year multi-centre study - Aldecoa, Yvonne S.; Alanazi, Adel; Saleh, Ghada Bin; Alshanbari, Nasser; Humayun, Tabish; Alsheddi, Faisal; El-Saed, Aiman; Alqahtani, Mohammed; H. Alanazi, Khalid (International Journal of Infection Control, 2022)
Background: The published rates of catheter-associated urinary tract infection (CAUTI) in Saudi Arabia were derived from single-centre studies or nationally non-representative studies. Objectives: The aim of this study was to estimate CAUTI rates and urinary catheter utilisation (UCU) ratios in 99 Saudi Ministry of Health (MOH) hospitals from all regions. Methods: A prospective surveillance study was conducted in 15 different types of intensive care units (ICUs) between January 2018 and December 2019. The data were entered into the Health Electronic Surveillance Network (HESN) programme. The methods of the US National Healthcare Safety Network (NHSN) and the Gulf Cooperation Council (GCC) centre for infection control were used. Results: During 2 years of surveillance covering 919,615 patient-days and 573,720 urinary catheter days, a total of 965 CAUTI events were identified. The overall MOH CAUTI rate was 1.68 (95%confidence interval (CI) 1.58–1.79) per 1,000 urinary catheter days, and the overall UCU was 0.624 (95%CI 0.623–0.625). CAUTI rates were highest in paediatric medical (5.73) and adult medical (2.02) ICUs. UCU were highest in neurosurgical (0.795) and medical surgical (0.743) ICUs. CAUTI standardised infection ratios across different ICUs in Saudi MOH hospitals were 16% lower than NHSN hospitals, 47% lower than GCC hospitals and 69% lower than International Nosocomial Infection Control Consortium (INICC) hospitals. Urinary catheter standardised utilisation ratios across different ICUs in Saudi MOH hospitals were 15% higher than NHSN hospitals, 9% higher than INICC hospitals and 13% lower than GCC hospitals. Conclusions: The current study is a unique national CAUTI benchmark that can potentially help in the fight against healthcare-associated infection.